Public health expenditure and household poverty: case study of Egypt - Marwa Biltagy; Manar Hamdi (Future Business Journal)
Abstract The insufficient and inefficient public expenditure on health services by any health system creates physical and financial barriers to using health care services, especially for poor people and uncovered informal sector workers. This leads to the appearance of household direct out-of-pocket (OOP) payments on health services. OOP will push households into poverty if it exceeds their monetary income, as they cut their spending on other essential needs such as food, clothing, or education fees. The main objective of studying public health expenditure is to provide essential health services to all citizens equally without pushing them into poverty due to health payments OOP. This paper examines the average coverage of Reproductive, Maternal, and Child Health (RMNCH) services according to place of residence and wealth quintile from 2005 to 2015. The rationale for choosing RMNCH only as an indication of health coverage is due to data limitations. This paper depends on World Health Organization (WHO) data. The paper evaluates poverty impact by using poverty head counts and poverty gaps before and after OOP through using nationally representative surveys of Egypt for the years 2005, 2009, 2011, 2013, and 2015. Results show a gap in covering RMNCH services among different groups, but the gap is decreasing over time. Results also show that OOP payments pushed on average 30% of Egyptian households into poverty during the period of the study.